(untitled) (University of Warwick Press, 2022)
This report describes the diversity of experiences of people with life-limiting illnesses who were supported by hospices in the West Midlands during the pandemic. It is one of four cohort reports – the others focus on patients, carers, and frontline hospice staff respectively – that form the evidence base for a Policy Report into the impact of Covid-19 on hospices. In these reports we address the nine key themes that were identified as potentially important in our previous collaborative knowledge synthesis (MacArtney et al., 2021) and seek to address some of the policy gaps we identified in our review of recommendations for hospice practice and policy (van Langen-Datta et al., 2022). Together these outputs are the result of an Economic and Social Research Council funded study (grant number: ES/W001837/1) that is one of the first studies to contribute an in-depth exploration of hospice-based experiences of the pandemic to the growing body of knowledge about the effectiveness and effects of changes to hospice services, at regional and national levels, in response to Covid-19. As the key decision makers during the Covid-19 pandemic, this part of the ICoH study aimed to explore senior managers’ experiences and to understand how they responded to the challenges imposed on them whilst still delivering a high-quality palliative care service. Coupled with hospice grey evidence in the form of, for example, senior management emails to staff, policy and guideline documents, we can start to understand the pressures and context in which decisions were made, including what worked well and what did not. The aim of this report is therefore to explore experiences of senior managers during the Covid-19 pandemic to identify recommendations for clinical practice and healthcare policy. Drawing on these findings, this report offers recommendations for hospices managers and clinicians who continue to provide care and support for people with life limiting conditions during the ongoing pandemic. These recommendations will also be of interest to local commissioners who will need to work with hospices in their region to ensure people with life-limiting conditions receive the support they need, and national policymakers who will need to ensure the necessary resources and guidance are available.